Dietary Diversity Indicators and Their Associations with Dietary Adequacy and Health Outcomes: A Systematic Scoping Review. Issue 5 (3rd March 2021) - Verger, Eric O; Le Port, Agnes; Borderon, Augustin; Bourbon, Gabriel; Moursi, Mourad; Savy, Mathilde; Mariotti, François; Martin-Prevel, Yves
Abstract: Dietary diversity has long been recognized as a key component of diet quality and many dietary diversity indicators (DDIs) have been developed. This systematic scoping review aimed to present a comprehensive inventory of DDIs and summarize evidence linking DDIs and dietary adequacy or health outcomes in adolescents and adults. Two search strategies were developed to identify peer-reviewed articles published in English up until June 2018 and were applied to Medline, Web of Science, and Scopus. A 2-stage screening process was used to select the studies to be reviewed. Four types of DDIs were identified among 161 articles, the majority of them belonging to the food group–based indicator type ( n = 106 articles). Fifty studies indicated that DDIs were proxies of nutrient adequacy, but there was a lack of evidence about their relation with nutrients to limit. Associations between DDIs and health outcomes were largely inconsistent among 137 studies, especially when the outcomes studied were body weight ( n = 60) and noncommunicable diseases ( n = 41). We conclude that the ability of DDIs to reflect diet quality was found to be principally limited to micronutrient adequacy and that DDIs do not readily relate to health outcomes. These findings have implications for studies in low- and lower-middle-income economies where DDIs are often used to assess dietary patterns and overall diet quality.